Professionalization of human resource development (HRD) practitioners in the Office of the Premier of the KwaZulu-Natal provincial government - Khuzwayo, Zamokwakhe Enock (My University, 2015)
Purpose: The purpose of this study was to solicit views of HRD practitioners regarding the Professionalisation and Recognition of Public Service Human Resource Development (HRD) Practice, using the experiences of HRD practitioners in the KwaZulu-Natal provincial government. Background: In recruiting employees into the public service, the South African Constitution dictates that policies that promote and maintain high standard of professional ethics should be applied. The principles of good human resource management and career-development practices, to maximise human potential, must be cultivated (South African Constitution, 1996). As such, a series of human resource development strategies were introduced from 2002 aimed at building the capacity of the state, with the latest of such, being the Public Service HRD Strategic Framework (PS-HRDSF): Vision 2015, having been introduced in 2007. The successful implementation of these strategies depended on the capacity of HRD practitioners in departments to drive these towards meeting their intended objectives, which is ensuring that the state has the capacity to deliver on its mandate. Amongst its priorities, the latest HRD strategic framework places premium on strengthening the capacity of HRD practitioners; by building a strong culture of professional practice in HRD. The aim is to create a sound foundation in public service institutions for the application of capacity development initiatives to enhance performance and improve service delivery (DPSA, 2007). Literature Review: The study visited the work of researchers in the HRD practice who have undertaken investigations into the true character of HRD as an independent practice which has its own body of knowledge and theory. Furthermore, the study visited the literature on challenges facing HRD in the future, such as the future survival of the HRD practice, recognition of HRD and its practitioners, and professionalisation of the practitioners. Methodology: The study, being of social science in nature and focusing into the topic of human development, was informed by a Critical Social Science (CSS) approach, in particular, the hermeneutic data analysis process. The study applied a mixed research method to ascertain (quantitatively), the views of HRD practitioners, ix professional bodies and policymakers to (qualitatively) understand their views on professionalisation. The collection of data was through a survey of HRD practitioners using questionnaires and unstructured interviews for HRD policymakers. Results: Using the hermeneutic data analysis process, the results were categorised into six themes: (1) Roles and competencies of HRD practitioners (2) Levels of growth experienced as a result of exposure to the implementation of HRD strategies in their respective departments within the province, (3) Recognition and professionalisation of HRD practitioners, (4) Common entry professional qualification into the HRD practice (5) Code of Conduct for HRD practitioners; and (6) Common Continuous Professional Development (CPD) for HRD practitioners. Recommendations: The research makes recommendations that HRD practitioners themselves should take initiatives to elevate the HRD practice through the development of the body of knowledge and theory. They should increase their efforts to redefine the role and contribution of the HRD function to the organisational performance improvement. They should form themselves into communities of experts and mobilise for the development of a Competency Dictionary for HRD practice as a basis for the DPSA to develop a Competency Framework. The same Framework will serve as the basis for continuous professional development.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.